An EWMA Control Chart for Monitoring the Mean of Skewed Populations Using Weighted Variance. - Khoo, Michael B. C.; Atta, Abdu M. A. (2008)

(untitled)
This paper discusses the use of weighted variance (wv) in setting up the limits of the exponentially weighted moving average (EWMA) chart for the monitoring of the mean of a process from a skewed population. This chart, called the WV-EWMA chart hereafter, reduces to the standard EWMA chart when the underlying distribution is symmetric.